Synthesis and Functionalization of Hexacoordinate (Arenediolato)bis(polypyridyl)silicon(IV) Complexes. Issue 18 (22nd May 2014) - Breiding, Tom; Henker, Jens; Fu, Chen; Xiang, Yonggang; Glöckner, Steffen; Hofmann, Philipp; Harms, Klaus; Meggers, Eric
Abstract: Hexacoordinate (arenediolato)silicon(IV) complexes that contain two additional 2, 2′‐bipyridine or 1, 10‐phenanthroline ligands are surprisingly stable against aqueous hydrolysis and therefore constitute attractive and novel templates for the design of bioactive compounds. In this article, we report the synthesis of (arenediolato)bis(polypyridyl)silicon(IV) complexes, including a case of diastereoselective synthesis of a nonracemic hexacoordinate (binaphtholato)silicon(IV) complex, and methods for their post‐coordinative functionalization with halides, nitro, and carbonyl groups. Several X‐ray crystal structures are provided and demonstrate the octahedral coordination of silicon in these complexes. Abstract : Synthetic methods for the post‐coordinative introduction of functional groups, namely, halides, nitro, and carbonyl groups, into hexacoordinate silicon(IV) complexes are reported that exploit the chemical robustness of (arenediolato)bis(polypyridyl)silicon(IV) complexes